THE ROLE OF INTEGRITY, WORKLOAD, WORK ETHIC ON EMPLOYEE PERFORMANCE IN THE FIELD OF PROCUREMENT, DISMISSAL, INFORMATION AND FACILITIES OF BKPSDM CITY OF BATAM: THE ROLE OF INTEGRITY, WORKLOAD, WORK ETHIC ON EMPLOYEE PERFORMANCE IN THE FIELD OF PROCUREMENT, DISMISSAL, INFORMATION AND FACILITIES OF BKPSDM CITY OF BATAM - Hardiantini, Rika; Satifali, Utrika; Syarini, Fitria; Hasim, Hasim; Indra, Jhoni; Roni, Roni (PENANOMICS: International Journal of Economics, 2024)
This study aims to examine the relationship between integrity, workload, and work ethic on employee performance in the Division of Procurement, Termination, Information, and Facilitation at the Batam Regional Civil Service Agency (BKPSDM), both individually and collectively. The population of this study consisted of all 32 employees in the aforementioned division, with no classification based on employee rank or status, as all employees were treated equally. The results indicate a significant positive influence of integrity, workload, and work ethic on employee performance. Improved integrity, higher workloads, and stronger work ethic among employees contribute to enhanced employee performance. The relationship between these variables is expressed through a multiple regression model, demonstrating how these factors collectively and individually impact performance. Validity and reliability tests confirmed that all instruments met the necessary criteria. Among the variables, work ethic had the most significant influence, suggesting it as the primary factor affecting employee performance.